Fiscal Multipliers : Size, Determinants, and Use in Macroeconomic Projections - Batini, Nicoletta (Technical Notes and Manuals; Technical Notes and Manuals ;, 2014)
Fiscal multipliers are important tools for macroeconomic projections and policy design. In many countries, little is known about the size of multipliers, as data availability limits the scope for empirical research. This note provides general guidance on the definition, measurement, and use of fiscal multipliers. It reviews the literature related to their size, persistence and determinants. For countries where no reliable estimate is available, the note proposes a simple method to come up with reasonable values. Finally, the note presents options to incorporate multipliers in macroeconomic forecasts.